Južnoameriška tripanosomoza - Chagasova bolezen - Bizjak, Tina (Medicinski razgledi, 2011)
It has been a century since the Brazilian physician Carlos R. J. Chages first described the basic morphology and life cycle of the American trypanosome, a parasite which causes Chagas disease. Chagas disease is a zoonosis caused by Trypanosoma cruzi. Trypanosoma cruzi is found mostly in blood-sucking triatomine insects and small mammals in areas ranging from the southern and southwestern United States to central Argentina and Chile. The acute phase of the infection usually passes unnoticed because it is symptom free or exhibits only mild, nonspecific symptoms and signs. After a latent period, 10-30 % patients develop signs of chronic infection with cardiac and gastrointestinal complications. Up to the mid-20th century, the epidemiology of the disease was closely linked to the extreme poverty of the peasant population and to their housing. In recent decades, however, the migration of the people from the countryside to towns has resulted in the urbanization of this rural disease. The increasing number of international travelers urges us to be alert to Chagas disease also in non-endemic regions.
Keywords: Chagas Disease; Chagasova bolezen; Kardiomiopatije; Trypanosoma cruzi; Megakolon; Cardiomyopathies; Megacolon; Požiralnik, ahalazija; epidemiologija; Esophageal Achalasia; diagnostika; klinična slika; therapy; zdravljenje